2016
DOI: 10.1039/c6em00392c
|View full text |Cite
|
Sign up to set email alerts
|

Highly time resolved chemical characterization of submicron organic aerosols at a polluted urban location

Abstract: Non-refractory submicron (NR-PM) aerosols were measured during the late winter period (February-March) via an Aerodyne High Resolution Time of Flight Aerosols Mass Spectrometer (HR-ToF-AMS) along with Black Carbon (BC) and trace gasses in an industrial city, Kanpur, situated in the Gangetic Plain (GP) of India. The composition of NR-PM aerosols was dominated by organics (54%), followed by inorganics (36%), and BC (10%). Source apportionment via Positive Matrix Factorization (PMF) of AMS measured organic aeroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…The share of BC in PM fractions was found to be ∼ 13 % in PM 1 , 9 % in PM 2.5 and ∼ 4 % in PM 10 but the correlation coefficients of BC with three PM fractions were found to be 0.89 (PM 1 ), 0.88 (PM 2.5 ) and 0.69 (PM 10 ), indicating the commonality in the sources of these pollutants. The contribution of BC in PM 1 was found to be ∼ 12 % in Kanpur during February-March (Kumar et al, 2016a), similar to Lumbini. Regarding the share of BC in PM 10 , the share observed in Lumbini (∼ 4 %) was similar to that observed over Varanasi (∼ 340 km south of our site) in central IGP (5 %) (Tiwari et al, 2016) and Dibrugarh in eastern IGP (∼ 5 %) (Pathak et al, 2013).…”
Section: Meteorologymentioning
confidence: 66%
“…The share of BC in PM fractions was found to be ∼ 13 % in PM 1 , 9 % in PM 2.5 and ∼ 4 % in PM 10 but the correlation coefficients of BC with three PM fractions were found to be 0.89 (PM 1 ), 0.88 (PM 2.5 ) and 0.69 (PM 10 ), indicating the commonality in the sources of these pollutants. The contribution of BC in PM 1 was found to be ∼ 12 % in Kanpur during February-March (Kumar et al, 2016a), similar to Lumbini. Regarding the share of BC in PM 10 , the share observed in Lumbini (∼ 4 %) was similar to that observed over Varanasi (∼ 340 km south of our site) in central IGP (5 %) (Tiwari et al, 2016) and Dibrugarh in eastern IGP (∼ 5 %) (Pathak et al, 2013).…”
Section: Meteorologymentioning
confidence: 66%
“…Earlier studies (e.g. Kumar et al, 2016;Thamban et al, 2017;Chakraborty et al, 2018 emissions over a village in the IGP, Fleming et al, (2018) have characterized a wide range of particle phase compounds 10 produced by traditional cook stoves and pointed out various organic compounds originate from these sources. Viewed in this context, dominance of organics in the IGP outflow is not surprising.…”
Section: Non-refractive Pm10 Mass Concentrationsmentioning
confidence: 99%
“…In Lumbini, the average (hourly) share of PM 1 in PM 2.5 , PM 1 in PM 10 and PM 2.5 in PM 10 was found to be ∼ 70, 34 and 47 %, respectively. Regarding other sites in IGP region, PM 2.5 / PM 10 ratios were reported to be 56 % in Kanpur (Snider et al, 2016), 60 % in Varanasi (Kumar et al, 2015), 57 % in Guwahiti (Tiwari et al, 2017), 90 % in Dribugarh (Pathak et al, 2013) and 62 % in Delhi , indicating local differences within IGP as well as suggesting that the influence of combustion sources at Lumbini is still lower compared to other locations in the Indian section of the IGP. A recent study (Putero et al, 2015) reported that the PM 1 / PM 10 during pre-monsoon of 2013 was found to be 0.39 in the Kathmandu Valley of Nepal.…”
Section: Meteorologymentioning
confidence: 96%